2014
DOI: 10.1188/14.onf.660-668
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Postmenopausal Breast Cancer Survivors on Adjuvant Endocrine Therapy-Related Symptoms

Abstract: Purpose To conduct an investigation of women's experiences related to taking AET and managing AET-related symptoms. Design Qualitative. Setting Main campus of the University of Pittsburgh. Sample Four groups with a total of 14 breast cancer survivors, aged ≥ 50 years with AET-related symptoms. Methods Semi-structured discussion guides were used to elicit recollections of conversations with health care providers about starting AET, symptom experiences, symptom management, and suggestions for improving m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(74 citation statements)
references
References 54 publications
5
68
0
1
Order By: Relevance
“…Prior studies have largely focused on patient perspectives, highlighting issues such as patient uncertainty in determining symptom origins, dissatisfaction with symptom management information received from providers, communication challenges, and unmet preferences for non-pharmacological symptom management approaches [21-23,45]. Our findings are consistent with and complement results from patient-focused studies.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Prior studies have largely focused on patient perspectives, highlighting issues such as patient uncertainty in determining symptom origins, dissatisfaction with symptom management information received from providers, communication challenges, and unmet preferences for non-pharmacological symptom management approaches [21-23,45]. Our findings are consistent with and complement results from patient-focused studies.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, although BC survivors often receive care from multidisciplinary healthcare providers (e.g., oncologists, nurses, psychologists), little is known about provider perspectives on barriers and facilitators to AET-related symptom management, as most previous studies have been limited to patient perspectives [21-23]. Given the shared role of patients and providers in the symptom management process, it is equally important to understand provider perspectives on factors influencing AET-related symptom management.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies suggest that survivors may be dissatisfied with patient-provider communication regarding AET symptom management. In a recent study examining AET symptom management experiences, survivors reported that providers were often dismissive of symptom concerns and failed to provide adequate information regarding symptom management [17]. …”
Section: Introductionmentioning
confidence: 99%
“…To date, most prior studies have obtained survivors’ perspectives on patient-provider communication regarding AET symptoms; yet, no studies, to our knowledge, have assessed provider perspectives on this care process [17, 29]. Providers’ communication skills play a key role in eliciting survivors’ report of symptoms and ensuring survivors’ adherence to long-term treatments such as AET [30].…”
Section: Introductionmentioning
confidence: 99%
“…These side-effects can have a significant impact on quality of life [37,38], and are often identified as drivers of non-adherence [7,39]. Studies suggest that women often feel unprepared for the side-effects and that they are given little support in dealing with them [40,41].Whilst the relationship between side-effects and adherence is not always consistent, qualitative research has shown that many women stop taking tamoxifen because of their side-effects [30,42].…”
Section: Stage 1: Needs Assessmentmentioning
confidence: 99%